Regulation of hippocampal long term depression by Neuroligin 1. (December 2018) - Dang, Rui; Qi, Junxia; Liu, An; Ren, Qiaoyun; Lv, Dandan; Han, Lifang; Zhou, Zikai; Cao, Feng; Xie, Wei; Jia, Zhengping
Abstract: Neuroligins (NLGs) are postsynaptic adhesion molecules known to play essential roles in synapse development and maturation, but their effects on synaptic plasticity at mature synapses remain unclear. In this study, we investigate the involvement of NLG1 in hippocampal long-term depression (LTD), a key form of long lasting synaptic plasticity, critical for memory formation and brain disorders, by using mice deficient in the expression of NLG1. We find that although NLG1 homozygous (NLG1−/−) mice show no impairments in either NMDA receptor- (NMDAR-LTD) or metabotropic glutamate receptor-dependent LTD (mGluR-LTD), the heterozygous (NLG1+/−) mice are significantly altered in both forms of LTD characterized by the absence of NMDAR-LTD but enhanced mGluR-LTD. Accordingly, the NLG1+/−, but not the NLG1−/− mice are altered in synaptic proteins, including PSD95, GluA2 and phosphorylated GluA1 at serine 845, all of which are involved in the expression of LTD. The NLG1+/− mice also exhibit autistic-like behaviors including increased grooming and impaired recognition memory. We further show that the expression of NLG3, a close family member of NLG1, is elevated in the NLG1−/−, but not in NLG1+/− mice, suggesting that the lack of LTD deficits in the NLG1−/− mice might be due to the increased NLG3. Our results reveal a gene dosage dependent role for NLG1 in the regulation of LTD and suggest that moderate changes in NLG1 protein level may be sufficient to cause synaptic and behavior deficits in brain disorders where copy number variants and hemizygosity of gene mutations are common. Highlights: NLG1 +/− mice, but not NLG1−/− mice, showed impairments in NMDAR-LTD. NLG1 +/− mice, but not NLG1−/− mice, showed enhanced mGluR-LTD. Both NLG1 +/− and NLG1−/− mice showed impairments in LTP. NLG1 +/− mice, but not NLG1−/− mice, showed deficits in contextual fear memory. Both NLG1 +/− and NLG1−/− mice are impaired in social memory.